Effects of Shade and Leachate from Invasive Chromolaena odorata (Siam Weed) on Seedling Growth and Development of Native Tree Species in Nepal - Sunita Poudel,; Ramesh Raj Pant,; Mukesh Kumar Chettri,; Lal Bahadur Thapa, (Tropical Life Sciences Research, 2025)
The weed Chromolaena odorata has negative impacts on invaded ecosystems. Canopy of its aerial parts and allelochemicals released by the weed can suppress the growth and survival of native species. Field assessment of native trees Aegle marmelos and Senegalia catechu evidenced that a declining trend of their seedlings under higher canopy of C. odorata. Experiments carried out in pots revealed the negative effects of the weed’s leachate and shade on growth and development of A. marmelos. The leachate increased proline levels in A. marmelos seedlings by ca. 33% in shade and 43% in light. Specific leaf area and secondary roots were decreased significantly under both light and shade conditions by leachate. In the light condition, leachate reduced seedling biomass by ca. 26% and root length by 16%. Shade alone decreased overall seedling growth, including leaf area and biomass with poor root growth and increased specific leaf area. Results showed that A. marmelos is susceptible to shade and C. odorata leachate during its early stage of growth and development. In addition to other factors contributing to the decline of A. marmelos population in nature, the invasion of C. odorata intensifies the challenge. Our study clarifies that the invasion of C. odorata in native habitat has further contributed to the population decline of native species alongside other contributing factors in nature. Hence, there is an urgent necessity to control and manage C. odorata to protect native species. Removal of C. odorata from the invaded site will be beneficial for approaching light for native seedlings as well as preventing the leaching substances into the soil.